2012
DOI: 10.1016/j.bmc.2012.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Indole alkaloids from two cultured cyanobacteria, Westiellopsis sp. and Fischerella muscicola

Abstract: Chemical investigation of two cultured cyanobacteria, Westiellopsis sp. (SAG strain number 20.93) and Fischerella muscicola (UTEX strain number LB1829) led to the isolation of three hapalindole-type alkaloids, namely hapalindole X (1), deschloro hapalindole I (2), and 13-hydroxy dechlorofontonamide (3), along with ten known indole alkaloids (hapalindoles A, C, G, H, I, J, and U, hapalonamide H, anhydrohapaloxindole A, and fischerindole L) and fischerellins A and B. The structures were determined by a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 24 publications
(25 reference statements)
0
46
0
Order By: Relevance
“…However, alkaloids are not widely used for disease therapy because most of the compounds mentioned exhibit carcinogenic properties and may cause severe toxicity to humans [94][95]. Chelerythrine of the group isoquinoline and hapalindole of the group indole are a few exceptions which exhibit antimicrobial activity against drug resistant strains such as towards P. aeruginosa at low dosages but indicate no toxicity in Vero cells [96][97].…”
Section: Alkaloidsmentioning
confidence: 99%
“…However, alkaloids are not widely used for disease therapy because most of the compounds mentioned exhibit carcinogenic properties and may cause severe toxicity to humans [94][95]. Chelerythrine of the group isoquinoline and hapalindole of the group indole are a few exceptions which exhibit antimicrobial activity against drug resistant strains such as towards P. aeruginosa at low dosages but indicate no toxicity in Vero cells [96][97].…”
Section: Alkaloidsmentioning
confidence: 99%
“…Several strains of the family Hapalosiphonaceae produce indole alkaloids [8]. The major classes of these indole alkaloids include hapalindoles, ambiguines, fischerindoles, and welwitindolinones, of which more than 80 variants have been described in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. They share several common motifs: an indole or oxindole core, a cyclohexane fused to that core, an isonitrile or isothiocyanate functional group, a chlorine substituent, or an additional ring [25].…”
Section: Inhibit T Cell Proliferationmentioning
confidence: 99%
“…Recently, it has been found that malyngolide interferes with bacterial quorum sensing (see section "Compounds interfering with bacterial quorum sensing"). The hapalindoles are a large compound family of related indole alkaloids that were first found in Hapalosiphon species [68][69][70], and were later also isolated from Fischerella [71,72] and Westelliopsis [72]. Hapalindoles show activity against a range of microorganisms including S. aureus, B. subtilis, Salmonella gallinarum, and E. coli [73].…”
Section: Metabolites With Direct Antibacterial Effectsmentioning
confidence: 99%
“…Interestingly, the various hapalindole congeners feature highly differing activity against a panel of microorganisms. The most potent compound, hapalindole A (2), shows MICs at sub-µM concentrations [72]. While having high antibacterial activity, they later have also been shown to be moderately cytotoxic [72] and highly insecticidal [74].…”
Section: Metabolites With Direct Antibacterial Effectsmentioning
confidence: 99%
See 1 more Smart Citation